2012
DOI: 10.1016/j.ecoleng.2012.01.013
|View full text |Cite
|
Sign up to set email alerts
|

In situ soil cementation with ureolytic bacteria by surface percolation

Abstract: The possibility of using microbiological processes to improve the mechanical properties of soil by undisturbed in-situ application has gained attention over recent years. This paper describes a new variation of in-situ soil reinforcement technology based on Microbially Induced Carbonate Precipitation (MICP), which involves both the hydrolysis of urea by soil bacteria enzyme and calcium carbonate precipitation in the presence of dissolved calcium ions. In contrast to other previously published approaches, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
114
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 275 publications
(136 citation statements)
references
References 18 publications
7
114
1
5
Order By: Relevance
“…The previous research (Cheng and Cord-Ruwisch, 2012) demonstrated that after primary treatments (2 flushes) a homogenous strength could be achieved in the 1 m fine sand column with 6 layers of bacterial placement. As discussed previously (Cheng and Cord-Ruwisch, 2012), with increasing column length a larger number of alternating layers of bacterial suspension and cementation solution for bacterial immobilization are needed.…”
Section: Fine Sand Columnsmentioning
confidence: 99%
See 2 more Smart Citations
“…The previous research (Cheng and Cord-Ruwisch, 2012) demonstrated that after primary treatments (2 flushes) a homogenous strength could be achieved in the 1 m fine sand column with 6 layers of bacterial placement. As discussed previously (Cheng and Cord-Ruwisch, 2012), with increasing column length a larger number of alternating layers of bacterial suspension and cementation solution for bacterial immobilization are needed.…”
Section: Fine Sand Columnsmentioning
confidence: 99%
“…Surface percolation associated with bacterial placement with multiple layers has been demonstrated in short columns (Cheng and Cord-Ruwisch, 2012). However, for large scale application depths of more than 1 m may need to be achieved.…”
Section: Cementation Of 2 M Columnsmentioning
confidence: 99%
See 1 more Smart Citation
“…6). It has been shown that MICP treated sands remain some porosity in materials (Cheng and Cord-Ruwisch 2012;Chu et al, 2012) and that good strength maintenance in seasonal water saturation and freeze-thaw is possible with porous materials (Cornforth 2005). Further studies may wish to investigate the permeability of hardened sands via S. ureae at various levels of CaCO 3 precipitation to strike a balance between 650 porosity, peak strength and endurance overtime in weather simulations.…”
Section: Environmental Durability Of Micpmentioning
confidence: 99%
“…Indeed, it has been 85 commented that the type of bacteria utilized is one of the major considerations and potential limitations in large scale geotechnical operations (Mitchell and Santamarina, 2005). Therefore, the search for new bacteria by which to achieve viable levels of MICP is important for optimizing the protocol best suited (in terms of performance, economics and environmental impact) for marketing in green industry (Cheng and Cord-Ruwisch 2012;Patel 2015;van Paassen et al, 2010). Following a literature review of the nine documented species of 90…”
Section: Introductionmentioning
confidence: 99%